1971
DOI: 10.1246/bcsj.44.2942
|View full text |Cite
|
Sign up to set email alerts
|

Studies of the Liquid-Liquid Partition Systems. VIII. Stabilities and Extractabilities of Copper(II) and Zinc(II) Complexes with Acetylacetone, Trifluoroacetylacetone, and Hexafluoroacetylacetone in Aqueous Sodium Perchlorate Solution-Carbon Tetrachloride Systems

Abstract: The distribution of copper(II) and zinc(II) chelates with three β-diketones, acetylacetone (AA), trifluoroacetylacetone (TFA), and hexafluoroacetylacetone (HFA) between carbon tetrachloride and aqueous sodium perchlorate solutions at 0.1m, 1m, and 3m has been determined at 25°C as a function of the concentration of the dissociated chelate anions. The stability constants for the metal chelates in the aqueous phase and the two phasedistribution constants for the uncharged complexes have been determined by a grap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1972
1972
2003
2003

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Furthermore, the model successfully predicted the inability of acetylacetone to extract copper in a single equilibrium stage even when used in large excess. For model calculations, the equilibrium constant data were obtained from Sekine and Ihara (8), and a model run was made for 35 °C and 96 atm. The computer model yielded an extraction efficiency of less than 1%, consistent with the observed phenomena.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the model successfully predicted the inability of acetylacetone to extract copper in a single equilibrium stage even when used in large excess. For model calculations, the equilibrium constant data were obtained from Sekine and Ihara (8), and a model run was made for 35 °C and 96 atm. The computer model yielded an extraction efficiency of less than 1%, consistent with the observed phenomena.…”
Section: Discussionmentioning
confidence: 99%
“…System selection was based on the availability of the input data necessary to model the system behavior. Solvent extraction of copper from aqueous solutions using carbon tetrachloride as a solvent was investigated in detail by Sekine and Ihara (8). The authors reported values of copper complex stability constants for acetylacetone and hexafluoroacetylacetone.…”
Section: Introductionmentioning
confidence: 99%
“…The nucleophilic attack of the pyrrolenine nitrogen is more advantageous for the CuL 2 complex with the more fluorinated L, because more positive charge on the Cu(II) ion is expected for CuL 2 with the less negative O atoms, which is the case of the CuL 2 complex with more fluorinated L. The electrostatic repulsion between the peripheral C 6 F 5 groups of H 2 tpfpp and the terminal substituents of L contributes to the faster Cu(II) ion incorporation for the CuL 2 complex, since the dissociation of the L - ligand from the Cu(II) center can be assisted by such repulsion. Furthermore, because the required energy to dissociate L - from the Cu(II) ion should be smaller for the CuL 2 complex with the more fluorinated L, as indicated by the stability constants for the formation of CuL 2 in aqueous solution, the activation process is considered to be much easier for the CuL 2 complex with the more fluorinated L. According to the above discussions, an expected feature of the transition state is depicted in Scheme .
2
…”
Section: Resultsmentioning
confidence: 99%
“…The standard enthalpies of formation of both of the chelating agents were assumed to be the same as that of acetylacetone, which was calculated by fitting the dissociation constants of acetylacetone in the temperature range 283-323 K (Liljenzin, 1969) to the van't Hoff equation. The complexation constant of Cu(TFA) 2 was obtained from Sekine and Ihara (1971). The complexation constant of Cu(FOD) 2 was treated as an adjustable parameter in the model.…”
Section: Resultsmentioning
confidence: 99%